2016
DOI: 10.1155/2016/9343417
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Peroxisomes in the Rice Blast Fungus

Abstract: The rice blast fungus, Magnaporthe oryzae, is a model plant pathogenic fungus and is a severe threat to global rice production. Over the past two decades, it has been found that the peroxisomes play indispensable roles during M. oryzae infection. Given the importance of the peroxisomes for virulence, we review recent advances of the peroxisomes roles during M. oryzae infection processes. We firstly introduce the molecular mechanisms and life cycles of the peroxisomes. And then, metabolic functions related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 63 publications
(125 reference statements)
0
30
0
1
Order By: Relevance
“…When cells are exposed by UV light and different oxidizing agents, peroxisome proliferation with the formation of tubular peroxisome and up-regulation of peroxins (PEX) related genes will be induced [73]. In M. oryzae , many peroxisome related genes are identified and influence pathogenicity [74]. We found that many up-regulated DEGs involving peroxisomes were enriched both in the WT and ∆ Momcp1 mutant (Table S9).…”
Section: Discussionmentioning
confidence: 98%
“…When cells are exposed by UV light and different oxidizing agents, peroxisome proliferation with the formation of tubular peroxisome and up-regulation of peroxins (PEX) related genes will be induced [73]. In M. oryzae , many peroxisome related genes are identified and influence pathogenicity [74]. We found that many up-regulated DEGs involving peroxisomes were enriched both in the WT and ∆ Momcp1 mutant (Table S9).…”
Section: Discussionmentioning
confidence: 98%
“…Up-regulation of large number of PEX genes in our study suggests a possible important role of these genes for S. sclerotiorum pathogenicity/ virulence. Fatty acid β-oxidation is a lipid metabolic pathway for degrading long chain fatty acids for nutrient and energy generation [102,103]. This is an enzyme mediated, four-step process pathway which results in acetyl-CoA, which can be fed into glyoxylate cycle or transported to mitochondria for energy generation through citric acid cycle.…”
Section: Peroxisome Associated Pathwaysmentioning
confidence: 99%
“…The glyoxylate cycle is important for gluconeogenesis, generation of glucose under nutrient scarce condition by assimilating the Acetyl-CoA generated via fatty acid β-oxidation. Isocitrate lyase (ICL1) and Maleate synthetase (MSL1) are two important enzymes of glyoxylate cycle [102]. ICL1 was found to be essential for the pathogenicity of another canola pathogen L. maculans [106]; and was shown to be important for full virulence of M. oryzae [107] and C. orbiculare [108].…”
Section: Peroxisome Associated Pathwaysmentioning
confidence: 99%
“…, Alternaria alternata and Fusarium sp. (Wang et al ., ; Fujihara et al ., ; Imazaki et al ., ; Goh et al ., ; Min et al ., ; Chen et al ., ) although the underlying mechanisms are not well known.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the disruption of structural genes of peroxisomes significantly attenuated virulence in several fungal species, including Magnaporthe oryzae, Colletotrichum sp., Alternaria alternata and Fusarium sp. (Wang et al, 2007;Fujihara et al, 2010;Imazaki et al, 2010;Goh et al, 2011;Min et al, 2012;Chen et al, 2016) although the underlying mechanisms are not well known.…”
Section: Introductionmentioning
confidence: 99%